Effects of empagliflozin in patients with chronic kidney disease from Japan: exploratory analyses from EMPA-KIDNEY - Nangaku, Masaomi; Herrington, William G.; Goto, Shinya; Maruyama, Shoichi; Kashihara, Naoki; Ueki, Kohjiro; Wada, Jun; Watada, Hirotaka; Nakashima, Eitaro; Lee, Ryonfa; Massey, Dan; Mayne, Kaitlin J.; et al. (Clinical and experimental nephrology, 2024)
EMPA-KIDNEY assessed the effects of empagliflozin 10 mg once daily vs. placebo in 6609 patients with chronic kidney disease (CKD) at risk of progression, including 612 participants from Japan.
Online veröffentlicht: 20. April 2024
Gesehen am 30.10.2024